PENGEMBANGAN MEDIA PEMBELAJARAN BERMUATAN KEARIFAN LOKAL BERBASIS AUGMENTED REALITY PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SDN 060858 TEMBUNG - Ramadhani Laili (STKIP Subang, 2026)
This study is motivated by the low learning outcomes of fourth-grade students at SDN 060858 Tembung on the topic of diversity in Pancasila. Most students have not achieved the minimum mastery criteria due to the continued use of conventional teaching methods and the limited use of innovative learning media, resulting in low student engagement and understanding. Therefore, more interactive and contextual learning media are needed. This study aims to develop an Augmented Reality (AR)-based learning media integrated with local wisdom for the topic “Understanding the Surrounding Environment.” The research method used is Research and Development (R&D), consisting of analysis, design, development, implementation, and evaluation stages. The results indicate that the AR-based learning media meets the criteria of validity, practicality, and effectiveness in improving student engagement and learning outcomes. Thus, AR-based learning media integrated with local wisdom can serve as an innovative solution to enhance the quality of learning in elementary schools.